SPORTS INJURY SURVEY ON BASKETBALL BRANCH ATHLETES IN UNIT KEGIATAN MAHASISWA STKIP PGRI JOMBANG BASKETBALL CLUB - Arsika Yunarta; Rahayu Prasetiyo (Universitas Majalengka, 2022)
This study aims to identify the types of sports injuries for basketball players in UKMSTKIPPGRI John Bang. The survey method is a descriptive method using the survey method. The subjects of this survey were UKM STKIP PGRI Jombang junior basketball players, totaling 35 people, and the survey sample consisted of 21 people with sampling criteria. The location of the survey was conducted at STKIPP GRI John Van's GOR Basketball Club. The survey tool used to collect the data in this survey was a written exam, and interviews and observations of the survey results were presented in tabular form. We collected data using a question-based interview test to get an idea of ​​the results of the survey. Based on data analysis, the results show that the types of injuries most often received by UKM STKIP PGRI Jombang junior athletes in basketball sports are knee injuries, ankle injuries (ankle) shoulder injuries, and up to 21 samples. Showed that they had 100% of these injuries, shoulder injuries 95.2%, hamstring injuries 18 cases, wrist injuries 85.7 cases 61.9%, elbow injuries 13 cases 57.1%, waist injuries 8 cases 38.1-6 finger injuries, 28.6%, heel injuries 5 cases, 23.8%.